Economic Growth, CO2 Emissions and Energy Consumption: The Turkish Case - Bozkurt, Cuma; Akan, Yusuf (International Journal of Energy Economics and Policy, 2014)
In recent years due to factors, such as increases in greenhouse and carbon dioxide (CO2) emissions, global warming and climate changes has become a major threat for all countries. So in order to prevent this increased environmental pollution and degradation CO2 emissions must be reduced. This study examines economic growth, CO2 emissions and energy consumption relationship in Turkey by using cointegration test. For this purpose 1960-2010 periods taken and annual data of Gross Domestic Product (Y), Carbon Dioxide Emissions (CO) and Energy Consumption (EC) are used. The obtained empirical results from this paper indicated that CO2 emissions effect negatively economic growth while energy consumption effect positively it. Keywords: Economic Growth; CO2 Emissions; Energy Consumption; Turkey; Cointegration Test. JEL Classifications: F43; Q43; Q56